The Intervention Scalability Assessment Tool: a pilot study assessing five interventions for scalability - Karen Lee (Public Health Research & Practice, 2020)
Objectives: This study tested the utility of the Intervention Scalability Assessment Tool (ISAT) with real-world interventions considered for scale-up in the Australian context. We explored user perceptions of the usefulness of the ISAT in making scalability decisions and conducted an analysis of completed ISATs.